The Influence of Sea Power Upon History 1660-1783 - I.C. Little (Scientia Militaria, 2012)
The author of this book, Alfred Thatcher Mahan, is to naval warfare what Clausewitz is to land warfare and his books are the source of many quotations and arguments over strategy, and above all, the meaning of seapower. It was thus with a feeling of renewing an old acquaintanceship that I approached this attractively bound green and gold book.